Biochemical Differentiation of Cocoa Cotyledon Proteins from Various Genetic Origins - Ismail, Amin (2000)
Previous studies have reported that differences in the cocoa flavour of roasted beans from various genetic origins do exist; however, the findings were mainly based on sensory evaluation. In addition, the cocoa flavours differences were also claimed to be solely due to the maternal plants and not to other factors such as physiological factors. Cocoa cotyledon contains vicilin (7S)-class globulin (VCG), a major storage protein. It is a native source of oligopeptides and free amino acids, both of which have been identified as precursors of specific-cocoa aroma. These precursors are formed by proteolysis during fermentation. The VCG and the splitting specificity of proteases from cocoa cotyledons have been known to be responsible in the production of cocoa-specific aroma precursors during fermentation. The separation patterns of VCG which were separately isolated from cocoa cotyledons of various genotypes namely Forastero, Criollo, Trinitario, PBC 140, SCA 12 and UITI are shown. Comparative studies of VCG patterns and its multiple forms were conducted by means of SDS-PAGE and two-dimensional electrophoresis (2-DIEF/SDS-PAGE), whereas oligopeptide profiles were detected using a high performance liquid chromatography. SDS-PAGE analysis of the molecular weights of the predominant polypeptides of VCG subunits (47 and 31 kDa) from various genotypes did not show qualitative differences. The 2-D IEF/SDS-PAGE analysis of the VCG subunits revealed at least 10 multiple forms with pIs in the range of 6.1 to 6.8. The additional polypeptides with their multiple forms which had pIs in the range of VCG subunits were also detected on 2-D IEF/SDS-PAGE. These polypeptides were most probably the resultant degradation proteolytic products from the action of aspartic endoprotease on VCG subunits. There were very strong similarities in the VCG subunits and their degradation products at the level of their polypeptide constituents from the standpoint of number, molecular weight and isoelectric point. The oligopeptide profiles of autolysis products of the acetone dry powder prepared from various genotypes did not revealed differences. It indicates that the action of aspartic endoprotease of the various cocoa genotypes on VCG during autolysis was similar. There was no analytical identity difference of VCG subunits and their degradation proteolytic products for all the genotypes. Thus, VCG seems not to be responsible for cocoa aroma differences in cotyledons of the various genotypes within methodical limits. The VCG was almost completely degraded as compared to the storage albumin at the end of fermentation. In conclusion, aroma differences in raw cocoa harvested from various genotypes are the result of other genotypes, physiological or curing related factors but are not due to genetic differences of aroma precursors derived from storage proteins.